2016
DOI: 10.1039/c5cp05447h
|View full text |Cite
|
Sign up to set email alerts
|

C–S@PANI composite with a polymer spherical network structure for high performance lithium–sulfur batteries

Abstract: A unique C-S@PANI composite with a conductive polymer spherical network (PSN) has been successfully designed and synthesized by a simple processing approach. The PSN framework is formed at the surface of the oxidized carbon black by conductive polymer self-assembly and grafting, followed by pouring elemental sulfur into the pores of the polymer matrix. As the cathode material for lithium-sulfur batteries, the C-S@PANI composite delivered a high specific capacity of 1453 mA h g(-1) at a 0.1 C current rate and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…[14,48] The peak at 1650 cm À1 is assigned to the stretching vibration of C=Og enerated from the oxidization reactions of catechol groups in DA molecules. [31,39] The surface composition of S/C@pDA composites is investigated by X-ray photoelectron spectroscopy (XPS)a nalysis. The survey scan spectrum demonstrates the existence of C, S, N and Oi nt he S/C@pDA composites (Figure 3d), consistent with the EDS analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,48] The peak at 1650 cm À1 is assigned to the stretching vibration of C=Og enerated from the oxidization reactions of catechol groups in DA molecules. [31,39] The surface composition of S/C@pDA composites is investigated by X-ray photoelectron spectroscopy (XPS)a nalysis. The survey scan spectrum demonstrates the existence of C, S, N and Oi nt he S/C@pDA composites (Figure 3d), consistent with the EDS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…porous carbon, carbon black, carbonn anofibers, carbon nanotubes and graphene), [24][25][26][27][28] and conductive polymers (e.g. polyethylene oxide, polypyrrole,a nd polyaniline) [29][30][31] are frequently employed as hosts for sulfur cathodes. As an example, Ji et al used hierarchical porousc arbonC MK-3 as the sulfur carrier, which not only supplies stable nanosized electrochemical reaction chambers, but also offersf ast electronic channelf or active material.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers have also been introduced to composite cathodes as a supplement to the formal polymer binder to modify the interface between the carbon and sulfur constituents and/or act as polysulfide hosts during battery operation . Conjugated polymers have been the focus of many examples implementing this strategy . An initial report by Yu et al demonstrated the use of poly(pyrrole) (PPy) nanowires as sulfur hosts.…”
Section: Cathodementioning
confidence: 99%
“…Others reported ball mixing, melt infusion, and vapour phase diffusion to achieve homogenous impregnation of sulphur into the pores [5,8,10]. Wrapping of carbon sulphur composites in various conductive polymers such as polyaniline and in conductive carbon matrices as graphene sheets was also realized with some success [19,26,27]. A promising strategy for the development of high-performance Li-S batteries relies on both S8 and S2-4 incorporation.…”
Section: Introductionmentioning
confidence: 99%